The Comparative study of the effects of crude extract from mao soi (antidesma acidum), bioflavonoid and alpha-tocopherol on oxidative stress in cats with chronic kidney disease - Kakanang Jaimun (Chulalongkorn University, 2013)
Thesis (M.Sc)--Chulalongkorn University, 2010